An Outer Membrane Vesicle‐Based Permeation Assay (OMPA) for Assessing Bacterial Bioavailability. Issue 5 (24th October 2021) - Richter, Robert; Kamal, Mohamed A. M.; Koch, Marcus; Niebuur, Bart‐Jan; Huber, Anna‐Lena; Goes, Adriely; Volz, Carsten; Vergalli, Julia; Kraus, Tobias; Müller, Rolf; Schneider‐Daum, Nicole; Fuhrmann, Gregor; et al.
Abstract: When searching for new antibiotics against Gram‐negative bacterial infections, a better understanding of the permeability across the cell envelope and tools to discriminate high from low bacterial bioavailability compounds are urgently needed. Inspired by the phospholipid vesicle‐based permeation assay (PVPA), which is designed to predict non‐facilitated permeation across phospholipid membranes, outer membrane vesicles (OMVs) of Escherichia coli either enriched or deficient of porins are employed to coat filter supports for predicting drug uptake across the complex cell envelope. OMVs and the obtained in vitro model are structurally and functionally characterized using cryo‐TEM, SEM, CLSM, SAXS, and light scattering techniques. In vitro permeability, obtained from the membrane model for a set of nine antibiotics, correlates with reported in bacterio accumulation data and allows to discriminate high from low accumulating antibiotics. In contrast, the correlation of the same data set generated by liposome‐based comparator membranes is poor. This better correlation of the OMV‐derived membranes points to the importance of hydrophilic membrane components, such as lipopolysaccharides and porins, since those features are lacking in liposomal comparator membranes. This approach can offer in the future a high throughput screening tool with high predictive capacity or can help to identify compound‐ and bacteria‐specific passive uptake pathways. Abstract : A filter support‐based model of the Gram‐negative bacterial outer membrane is developed employing outer membrane vesicles from a porin‐containing and porin‐deficient Escherichia coli strain. Permeation data obtained from outer membrane vesicle‐derived models are in better agreement with reported data on bacterial bioavailability than permeation data obtained from liposomal comparator models.